2009
DOI: 10.1016/j.nbd.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl sulfoxide (DMSO) produces widespread apoptosis in the developing central nervous system

Abstract: Dimethyl sulfoxide (DMSO) is a solvent that is routinely used as a cryopreservative in allogous bone marrow and organ transplantion. We exposed C57Bl/6 mice of varying postnatal ages (P0–P30) to DMSO in order to study whether DMSO could produce apoptotic degeneration in the developing CNS. DMSO produced widespread apoptosis in the developing mouse brain at all ages tested. Damage was greatest at P7. Significant elevations above the background rate of apoptosis occurred at the lowest dose tested, 0.3 ml/kg. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 48 publications
8
152
4
2
Order By: Relevance
“…This delay in axonal regeneration could be due to the effect of DMSO that was used as solvent. Studies have shown that DMSO affects the structure and functions of sciatic nerve in rats [96], and induces apoptosis in the mouse brain [97]. My findings support the results of previous studies, which have shown that nerve injury upregulates LC3 [98,99].…”
Section: Resultssupporting
confidence: 88%
“…This delay in axonal regeneration could be due to the effect of DMSO that was used as solvent. Studies have shown that DMSO affects the structure and functions of sciatic nerve in rats [96], and induces apoptosis in the mouse brain [97]. My findings support the results of previous studies, which have shown that nerve injury upregulates LC3 [98,99].…”
Section: Resultssupporting
confidence: 88%
“…solution in sterile saline) twice at 0 h and 2 h. DMSO (SigmaAldrich, St. Louis, MO) (5 ml/kg or 10 ml/kg) was injected intraperitoneally into P7 C57BL/6By mice according to a method that induces neurodegeneration in P7 mice ( 39 ). Two microliters of saline or LPS (Sigma-Aldrich; serotype, 0127:B8) (1 mg/kg) in saline were injected intracerebrally into P7 C57BL/6By mice according to a method that induces brain injury, including astrogliosis, in P5 rats ( 40 ).…”
Section: Gm2 Elevation In Activated Gliamentioning
confidence: 99%
“…We then tested the possibility that treatments other than ethanol, which are known to induce neurodegeneration and/or glial activation, increase GM2 levels in the developing brain. It has been shown that DMSO, like ethanol, induces neurodegeneration in P7 mice ( 39 ). Therefore, lipid profi les of the brain harvested 24 h after the intraperitoneal injection of DMSO into P7 C57BL/6By mice were analyzed as described in the Materials and Methods.…”
Section: Gm2 Elevation Occurs In Microglia And/or Astrocytes Of P7 MImentioning
confidence: 99%
“…Even at a concentration as low as 0.5%, DMSO could lead to apoptosis in the central nervous system, and at the postnatal age of 7 and 30 which are equivalent to human childhood ages, severe damage was observed after DMSO exposure. 46 Therefore, as the peak incidence of osteosarcoma in adolescents is in 10-14-year-olds, when pubertal growth starts, 4 DMSO might cause damage in the central nervous system when used as a solvent for hydrophobic anticancer drugs. In this study, APNPs did not show significant toxicity, so the curcumin-loaded APNPs could accelerate the internalization of curcumin with low toxicity induced by short polypeptides, although further in vivo studies are required to investigate this.…”
Section: Discussionmentioning
confidence: 99%